On instability of conservative systems with gyroscopic forces - Sosnitskii, S. P. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
Theorems on equilibrium instability of conservative systems with gyroscopic forces are proved. The theorems obtained are nonlinear analogs of the Kelvin theorem. The equilibrium instability of the Chaplygin nonholonomic systems is considered.